Does social reporting matter? Empirical evidence. Issue 4 (20th May 2021) - Sarea, Adel; Salami, Monsurat Ayojimi
Abstract : Purpose: This paper aims to examine the level of Islamic social reporting (ISR) disclosure of Islamic banking in Gulf Cooperative Council (GCC) countries using a checklist based on Accounting and Auditing Organization for Islamic Financial Institution (AAOIFI) standards. Design/methodology/approach: A quantitative method – Tobit Model – is adopted in this study. The unweighted disclosure method used to measure the ISR disclosure checklist consist of 51 items in Islamic banks (IBs) in the GCC countries. The stakeholder theory and legitimacy theory are used to investigate the possible banking performance factors affecting the accounting practices such as ISR disclosure in IBs. Findings: The findings show that the ISR disclosure index is linked to the IBs' performance indicators in GCC countries. The result indicates both Islamic banking profitability and age establish positive and statistically significant relationship with ISR disclosure while leverage establishes significant negative relationship with ISR disclosure. This implies that Islamic banking profitability, leverage, and age are essential bank performance indicators that make ISR disclosure worthy of doing even in the presence of Islamic bank stakeholders in GCC countries. This finding linked compliance with the mandatory disclosure recommendations of AAOIFI Standard No. 7, as well as voluntary disclosure. Research limitations/implications: This study used cross sectional data for the year 2019, which is considered more recent despite its being a year data analysis. However, future research should consider mix method as well as more analysis tools provided their number of observations are sufficient enough. Social implications: The study identifies the factors that may enhance Islamic financial institutions, including Islamic banking in GCC countries, to comply with ISR disclosure. The application of this study supports Accounting standards setters to consider standards that support ISR disclosure in Islamic banking in different countries. Originality/value: To the best of the authors' knowledge, this study is novel in exploring the level of ISR disclosure in Islamic banking in GCC countries by using a checklist based on AAOIFI standard No. 7 and establishes the relationship between ISR disclosure index and IBs profitability, leverage, as well as age of Islamic banking in operation.